PENGARUH UMPAN BALIK POSITIF PEMIMPIN DAN PENILAIAN KINERJA TERHADAP PERILAKU INOVATIF KARYAWAN: PERAN MEDIASI PERILAKU SUARA DAN OTONOMI PEKERJAAN - Dodi Ria Atmaja; Arfia Damayanti (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to examine the effect of positive leader feedback and performance appraisal on employee innovative behavior mediated by voice behavior and job autonomy. The sample in this study involved 140 respondents who are employees in manufacturing, distribution and service companies. This study uses a quantitative approach which then uses primary data obtained from the results of filling out questionnaires via google form. The data were analyzed using data processing techniques using the Lisrel Structural Equation Model (SEM) method. Based on the results of the analysis in this study, it is known that innovative behavior can be influenced by positive feedback from leaders and performance appraisals which are proven to be mediated by voice behavior and job autonomy. It is thus concluded that positive feedback from leaders and performance appraisals has an important role in encouraging employees to behave innovatively supported by communication from employees through voice behavior and job autonomy.Keywords: Leader Positive Feedback(LPF), Performance Appraisal(PA), Innovative Behavior(IB), Voice Behavior(VB), Job Autonomy(JA).